The Trend of Integrated Capitals Reporting: The Asian Perspective - Abang, Salihin; Anifowose, Mutalib; Zakari, Muntaka Alhaji (Asian Journal of Accounting Perspectives, 2020)
Research aim: This paper examines the trend of integrated capitals reporting in Asia, given the introduction of the integrated reporting (IR) framework in some of the countries across the continent. Design/ Methodology/ Approach: Using content analysis, the study examines the quality and extent of IR capital reporting based on IR capitals checklist developed based on the International Integrated Reporting Council’s (IIRC) framework. The data were drawn from 332 integrated reports hosted on the website of IIRC related to listed companies across the Asian continent over a four-year period (2015-2018). Research finding: The findings indicate a significant increase in the extent and quality of IR capitals disclosure. It also shows significant improvements in each element of IR capitals such as human capital, intellectual capital, social and relationship capital and natural capital based on the sampled integrated reports. Furthermore, financial capital is the most disclosed capital, while manufactured capital is the least disclosed. Though there is a significant increase in the level of disclosure, the extent of disclosure is more pronounced compared to that of the quality of disclosure. Theoretical contribution/ Originality: This study provides a scientific conclusion on the trend of IR capitals disclosure in the Asian continent using most recent integrated reports. Practitioner/ Policy implication: The findings would assist those charged with governance to monitor their reporting strategies about the IR capitals. It helps to point out the areas of improvement in disclosing each element of the IR capitals. The IIRC would also appreciate the trend of quality and extent of IR capital reporting in the Asian continent. This would, in turn, help in the review for any improvement needed to the framework. Keywords: Asia, Integrated Reporting, Multiple Capitals, Content Analyses, Trend Analyses Type of article: Research Paper JEL Classification: M41, M42